2018
DOI: 10.1108/ijcst-07-2017-0097
|View full text |Cite
|
Sign up to set email alerts
|

An efficient termination control strategy of air-vented dryer for fabric drying

Abstract: Purpose The purpose of this paper is to develop an efficient termination control strategy of air-vented dryer in term of energy saving, improving smoothness and reducing microscopic damage of fiber. Design/methodology/approach A simple, low cost termination control strategy is developed by testing the instantaneous humidity of exhaust air and then deducing the drying degree of fabric in process. The practicability evaluation of this novel strategy was investigated by using both experimental and mathematical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, a study on movement comparison at various flow rates, heater voltages, and loads confirmed that the movement of the entire drum increases with a faster flow rate and smaller load. 4 , 5…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a study on movement comparison at various flow rates, heater voltages, and loads confirmed that the movement of the entire drum increases with a faster flow rate and smaller load. 4 , 5…”
mentioning
confidence: 99%
“…Furthermore, a study on movement comparison at various flow rates, heater voltages, and loads confirmed that the movement of the entire drum increases with a faster flow rate and smaller load. 4,5 Yu et al proposed a drying program that reduced the energy consumption with a lower air flow rate in the initial drying stages, and then the drying speed was increased with an increasing air flow rate in the latter stages. 6 Through this approach, the drying efficiency was increased; however, the fabric shrinkage and damage were intensified.…”
mentioning
confidence: 99%